Three‐layer coordinated control of the hybrid operation of static var compensator and static synchronous compensator. Issue 9 (1st June 2016) - Li, Mingming; Li, Wenlei; Zhao, Jia; Chen, Wei; Yao, Wanting
Abstract : Aiming at the problems that static var compensator cannot suppress the voltage flicker and the cost of static synchronous compensator is expensive, a three‐layer hybrid reactive power compensation scheme was proposed in this study based on the expert‐decision, differential‐slope voltage regulation, and the expert‐decision subsystem combining with fuzzy self‐tuning proportional–integral (PI) control. By switching in a dynamic load which can always change the bus voltage, the whole system was simulated under the much reactive power shortage and the less shortage. The simulation results verify the effectiveness of the proposed coordinated control method in the reactive compensation and the suppression of the voltage flicker.